Caracterização bioquímica da urina de pacientes diabéticos e pacientes hipertensos por Espectroscopia no Infravermelho com Transformada de Fourier (FTIR-ATR) - (:unkn) unknown (Universidade Brasil, 2022)
The evaluation of biological fluids by optical techniques has shown great importance in the diagnosis or monitoring of several pathologies. In this context, the evaluation of urine can provide several biochemical information, which when associated with the patient's clinical condition, allows to find markers for the disease or understand its behavior. In addition, urinary material is easy to be collected, which, in most cases, is a quick and non-invasive process. Thus, this study aimed to analyze the urinary material of healthy, diabetes mellitus and hypertension participants, to understand the possible biochemical changes present in each case. For this purpose, 65 urine samples from 20 healthy patients (SAU), 20 diabetic patients (DIA) and 25 hypertensive patients (HAS) were evaluated. The equipment used was an ALPHA’s Platinum ATR System spectrometer (Bruker, Germany) equipped with an ATR unit. The urine samples, after being homogenized and at room temperature, were inserted on the equipment's diamond crystal and the signal was acquired with 32 scans at a wavelength of 1000 - 4000 cm-1 , with a resolution of 4 cm-1 . After signal acquisition, all spectra were pre-processed with the background subtraction and normalized by the urea peak (1468 cm-1 ). The data were initially evaluated by the spectral averages of each group for the identification and choice of the main biochemical components to be evaluated, followed by the calculation of the area under the curve (AUC) using the second derivative spectra of these same components. The statistical methods used were the Student's T Test and the Mann Whitney test, always considering the normal data distribution. The p value used in the study to verify statistical significance was p ≤ 0.05. The results obtained showed changes in the concentration of glucose, proteins, lipids, carboxymethylisin (CML) and urea. All of these elements showed increases and/or decreases in concentration between groups, depending on the peaks evaluated. Despite the different concentrations observed between the groups for the biochemical components evaluated, statistically differences were found only in the glucose concentration between the HAS x DIA groups (p = 0.014), in the CML concentration between the HAS x SAU groups (p = 0.012) and in the concentration of lipids between the HAS and DIA groups (p = 0.031). Thus, we have shown that evaluation of urine as a source of information through the FTIR technique allowed us to understand and find differences between various biochemical components in samples from healthy, diabetic and hypertensive individuals. In addition, this type of analysis may, in the future, be widely used, in order to identify the concentration of marker elements, enabling a faster diagnosis or follow-up for many pathologies.
Keywords: FTIR; Diabetes mellitus; Hipertensão; Urina; Engenharia Biomédica (Bioengenharia)